Expanding known global biodiversity of Yamaguticestus (Cestoda: Phyllobothriidea) parasitizing catsharks (Pentanchidae and Scyliorhinidae). Issue 7 (3rd October 2021) - Caira, J. N.; Pickering, M.; Jensen, K.
Abstract : This paper aimed to test the prediction that substantial undiscovered biodiversity in the tapeworm genus Yamaguticestus Caira, Bueno & Jensen, 2021 exists in the 16 of 18 genera of catsharks globally that have not yet been examined for tapeworms. A total of 200 catsharks of 10 species representing eight genera were sampled opportunistically from the waters off Australia, Chile, Malaysian Borneo, South Africa, South Korea, and the UK between 1991 and 2017. Six species in four genera (i.e., Apristurus Garman, Asymbolus Whitley, Holohalaelurus Fowler, and Scyliorhinus Blainville) were found to host a total of six new species of Yamaguticestus, tripling the number of described species. The new species are Yamaguticestus africanae sp. nov. from Scyliorhinus capensis, Yamaguticestus ellisi sp. nov. from Scyliorhinus canicula, Scyliorhinus fairweatherae sp. nov. from Holohalaelurus regani, Yamaguticestus kihongkimi sp. nov. from Scyliorhinus torazame, and Yamaguticestus kuchtai sp. nov. from Apristurus aphyodes . The new species were characterized using a combination of light and scanning electron microscopy; sequence data for the D1–D3 region of the 28S rRNA gene were generated for five of the species. Transfer of a species formerly assigned to Calyptrobothrium Monticelli, 1893 that is morphologically consistent with Yamaguticestus added Cephaloscyllium Gill to the list of catshark genera known to host this genus. Most tapeworm species exhibited a remarkably low prevalence and intensity of infection suggesting that our failure to detect infection in the four genera of sharks represented by small sample sizes may not be indicative of their unsuitability as hosts. Our results suggest that the earlier prediction that 70 species of Yamaguticestus remain to be discovered in catsharks across the planet may actually be an underestimate. http://zoobank.org/urn:lsid:zoobank.org:pub:63F48CF6-ED06-44FC-839D-